What Turkish Teachers/Preservice Teachers Should Read? -A Suggested Book List - Arici, Ali Fuat (HACETTEPE UNIV, 2015)
Reading is a skill that must be developed permanently in order to realize one self and to keep up with the times. For this, especially Turkish teachers must be good reader and then it is necessary to instill reading habit to students. Main purpose of this research is to specify books which are considered beneficial to read by Turkish teacher and preservice Turkish teacher. For this purpose, interviews were conducted with 25 faculty members who are working in six different universities' Turkish language education department and 25 Turkish teachers working in MoNE. In determining the participants in the study snowball sampling technique was used. To collect data of research, semi-structured data collection tool was developed. Descriptive analysis techniques were used while analyzing the data collected. At the end of the study, the majority of participants stated that Turkish teachers and preservice Turkish teachers don't read books regularly. So they noted that we must have book suggestion list for professional groups. Also, in accordance with the opinion of the participants a suggestion list consists of 100 books has been identified and they have been justified.
Keywords: Turkish teachers; reading; book list; Turkish language education; HABITS; Education & Educational Research